Chronological index of the works by Nikolai I. Vavilov published in the journal Proceedings on Applied Botany, Genetics and Breeding - article Editorial (Труды по прикладной ботанике, генетике и селекции)
The index of Nikolay Vavilov’s works includes publications in the journal Proceedings on Applied Botany, Genetics and Breeding from the first one in 1913 to the last in 1938. In 1991, the editors of Proceedings considered the expediency of reprinting Vavilov’s article Near the Pamirs (Darvaz, Roshan, Shugnan): an agronomic sketch, previously published in an issue of the Tajik Academy of Sciences (1964). The preface to this publication explained that the report on the collecting mission to the Pamirs in 1916 was found in Nikolay Vavilov’s archives and submitted for publication by his son, Yury Vavilov. The decision to republish the report in Proceedings on Applied Botany, Genetics and Breeding was supported by the fact that this work was little known to a wide community of readers. The article was published in Vol. 140 dedicated to the 75th anniversary of Vavilov’s first collecting missions.